Factors affecting micro, small, and medium-sized enterprise development in developing Asia: Findings from a probabilistic principal component analysis - Shigehiro Shinozaki; Daisuke Miyakawa; Romeo Arahan (Asian Development Bank (ADB), 2024)
Limited data on micro, small, and medium-sized enterprises (MSMEs) make it difficult for governments to design appropriate MSME policies in Asia and the Pacific. To identify factors affecting MSME development and promote evidence-based policymaking, we propose a probabilistic principal component analysis method that works despite current data limitations. The study uses time-series MSME data collected from 25 developing member countries of the Asian Development Bank (ADB) through the Asia Small and Medium-Sized Enterprise Monitor project. The estimation results suggest that sound MSME credit markets, diversified financing options, support for new businesses and job creation, and active MSME participation in global marketplaces play a critical role in ensuring a smooth business recovery from various crises and shocks affecting developing Asia and the Pacific.
Keywords: D22; G20; L20; L50; 330; SME development; access to finance; financial inclusion; SME policy; probabilistic principal component analysis; Southeast Asia; South Asia; Central and West Asia; the Pacific